2017
DOI: 10.1016/j.ejvs.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Contralateral Deep Venous Thrombosis after Iliocaval Venous Stenting

Abstract: Stent placement across the iliocaval confluence from the left CIV is associated with a low but definite rate of contralateral iliac vein thrombosis. Acute DVT, pre-operative contralateral IIV thrombosis, pre-existing IVC filters, and anticoagulation non-compliance are significant risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 16 publications
0
16
0
2
Order By: Relevance
“…With the accumulated experience of intervention treatment of iliac vein occlusion, many studies suggest that contralateral venous thrombosis should not be ignored after the stent is positioned in the IVC. The incidence of contralateral venous thrombosis was approximately 1.1% to 2.7% 8,9,10 It is reported that the incidence of contralateral iliac vein thrombosis will increase due to the following factors: hypercoagulable state, contralateral internal iliac vein thrombosis, placement of vena cava filters before iliac vein stenting, and nonstandard anticoagulation therapy. 8,9 In our previous experimental study, we observed that when the iliac vein stent was entered into the IVC and completely covered the contralateral iliac vein ostium, intimal hyperplasia occurred in the stent strut covering the ostium of the contralateral iliac vein in the short term but did not affect the contralateral blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the accumulated experience of intervention treatment of iliac vein occlusion, many studies suggest that contralateral venous thrombosis should not be ignored after the stent is positioned in the IVC. The incidence of contralateral venous thrombosis was approximately 1.1% to 2.7% 8,9,10 It is reported that the incidence of contralateral iliac vein thrombosis will increase due to the following factors: hypercoagulable state, contralateral internal iliac vein thrombosis, placement of vena cava filters before iliac vein stenting, and nonstandard anticoagulation therapy. 8,9 In our previous experimental study, we observed that when the iliac vein stent was entered into the IVC and completely covered the contralateral iliac vein ostium, intimal hyperplasia occurred in the stent strut covering the ostium of the contralateral iliac vein in the short term but did not affect the contralateral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of contralateral venous thrombosis was approximately 1.1% to 2.7% 8,9,10 It is reported that the incidence of contralateral iliac vein thrombosis will increase due to the following factors: hypercoagulable state, contralateral internal iliac vein thrombosis, placement of vena cava filters before iliac vein stenting, and nonstandard anticoagulation therapy. 8,9 In our previous experimental study, we observed that when the iliac vein stent was entered into the IVC and completely covered the contralateral iliac vein ostium, intimal hyperplasia occurred in the stent strut covering the ostium of the contralateral iliac vein in the short term but did not affect the contralateral blood flow. 3 However, in the present study, we extended the observation period to 12 months after stenting and found that the bare stent covering the ostium of the contralateral iliac vein was covered by the proliferating intima, which had partially transformed into mature endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case of subacute iliocaval occlusion, the size of the residual thrombus burden was too great for an uncovered bare metal stent to be used. Using uncovered stents within the iliocaval confluence would also increase the likelihood for contralateral iliac vein and post-procedural deep vein thrombosis to occur [9]. Furthermore, a covered aortic stent graft was used to reduce the risk of excluded thrombus penetration through the stent interstices, as would be the case in an uncovered stent.…”
Section: Discussionmentioning
confidence: 99%
“…Another is the area of thrombotic damage. For example, endovenous stenting within the iliocaval confluence has been reported to cause contralateral iliac vein and post-procedural deep vein thrombosis [9]. However, both challenging anatomical areas, such as the iliocaval confluence, and extensive thrombotic occlusion can be addressed when considering venoplasty and venous reconstruction in chronic or acute iliocaval disease, according to recently documented novel interventional approaches.…”
Section: Introductionmentioning
confidence: 99%